High-velocity nasal insufflation in the management of overlap syndrome: a randomized clinical trial - Lamiaa Hassan Shaaban; Ashraf Zin EL-Abdeen Mohamed; Abanoub Hany Sadek; Waleed Gamal Elddin Khaleel (The Egyptian Journal of Bronchology)
Abstract Background High-velocity nasal insufflation (HVNI) has emerged as an effective method for delivering ventilatory support. Its ability to clear extra-thoracic dead space justifies HVNI use for hypercapnic respiratory failure. This study aims to investigate the effectiveness of HVNI in managing the overlap syndrome subgroup of patients presenting with hypercapnic respiratory failure. Methods This parallel randomized controlled study was performed on 46 overlap syndrome patients (combined COPD and OSA). Overlap syndrome patients who presented with hypercapnic respiratory failure were recruited from respiratory ICU between March 2023 and June 2024. Patients were randomly allocated to receive ventilatory support into either group A (HVNI group) or group B (NIV group). Patients were monitored clinically utilizing modified Borg dyspnea scale and arterial blood gas parameters. ICU and hospital outcomes for both groups were also pursued. Results HVNI implementation among acutely exacerbating overlap syndrome patients was as effective as NIV in control of dyspnea and ABG parameters. HVNI showed significantly lower PaCO2 compared to NIV group (P = 0.042) after 24 h follow-up. After 48 h of follow-up, all arterial blood gas parameters were comparable between both studied groups with no significant difference between them (P > 0.05). Facial ulceration, agitation, and anxiety were significantly higher among NIV group (P < 0.001). Conclusions High-velocity nasal insufflation (HVNI) is an effective treatment option for managing acutely exacerbating overlap syndrome (COPD and OSA) patients with hypercapnic respiratory failure. HVNI demonstrates a comparable ability to reduce hypercapnia, improve oxygenation compared to noninvasive ventilation (NIV), and HVNI enhances patient comfort and compliance more efficiently. These findings support the use of HVNI as a valuable alternative in clinical settings, particularly for patients who struggle with the discomfort and complications associated with NIV use. Trial registration ClinicalTrials.gov. NCT05190458.